PROBLEMS AND PROSPECTS OF INTEGRATION OF DATA GOVERNANCE WITH MULTICLOUD PLATFORMS (American Journal of Technology and Applied Sciences, 2025)
This article examines the key issues and prospects for integrating data management practices (Data Governance) in multi-cloud environments. The main challenges arising in the context of multi-cloud architectures are identified and systematized, including technical, organizational and legal aspects. An analysis of the impact of multi-clouds on data management processes is conducted, and approaches to overcoming the identified difficulties are proposed. In conclusion, strategic directions for further research and practical development in this area are outlined, which allows for the formation of a comprehensive vision of solving the problem of ensuring data integrity and security in distributed cloud infrastructures.